THU0264 Efficacy and Safety of Cyclosporine-A During Pregnancy in Autoimmune Diseases. (23rd January 2014) - Reggia, R.; Andreoli, L.; Bazzani, C.; Nuzzo, M.; Tincani, A.
Abstract : Background: Cyclosporin-A (CYS-A) is an immunosuppressant agent widely used in the context of anti-rejection therapy. In Rheumatology it's indicated for Rheumatoid Arthritis (RA) and Psoriasic Arthritis (PA), but it's also administered to control other connective tissue diseases like Systemic Lupus Eritematosus (SLE) and Dermatomyositis (DM) and in patients suffering from vasculitis. These diseases often occur in fertile women, therefore, in recent years, the compatibility of the drug with pregnancy has been largely debated. FDA classifies CYS-A in class C, since there are no conclusive data about it's safety and not recommended breastfeeding during therapy, even though several registries and retrospective studies seem to demonstrate its safety [1, 2 ]. Most of the available data derive from exposed pregnancies in transplanted women [3 ] and no studies have shown adverse effects on newborns [4 ]. Objectives: To analyze a series of patients suffering from autoimmune diseases, treated with CYS-A during pregnancy and to highlight any related maternal-fetal complications. Methods: 25 pregnancies in 19 consecutive patients treated with CYS-A throughout gestation was analyzed, focusing on demographic characteristics, underlying disease activity and the onset of maternal and/or fetal complications. Results: At the time of pregnancy, patients had an average age of 32.2 years and underlying diseases in stable remission. They suffered from RA (n=2), PA (n=2), SLE (n=13, 1with associated Kikuchi disease), Sjögren Syndrome (n=1), DM (n=1). Therapy was made of CYS-A, 3mg/kg (tapered to suspension before delivery in 5 patients: 20%), low-medium dosage steroids(n=20: 80%), aspirine (n=22: 88%), hydroxychloroquine (n=17: 68%), azathioprine (n=1: 4%) and low molecule weight heparin (n=4: 16%). We had 20 full-term pregnancies (80%), with a mean gestational age of 38weeks, 1 is still ongoing.1 PROM (4.8%) and 2 IUGR (10%), both evolved into SGA babies. 3 Spontaneous Abortions (12%)and 1 voluntary abruption because of the finding of Turner's Syndrome and cystic hygroma (4%).11 pregnancies (55%) resulted in natural delivery, 9 (45%) in caesarean section. Newborns presented a mean birth-weight of 2857g and they all had normal apgar scores. We found 2 (10%) maternal disease flares during gestation and 2 (10%) in puerperium. 2 cases of gestational hypertension (1 of new onset) and 2 (10%) elevations of pre-existing proteinuria. Conclusions: According to existing data we found no evidences justifying the suspension of CYS-A when a pregnancy occurs. The drug does not appear to increase maternal-fetal complications comparing with general population(PROM:4.8%vs10%, IUGR:10%vs4-8%, Gestational hypertension:10%vs4-10%)and it should be continued in patients who benefit from therapy. When possible, the drug should be tapered to suspension to allow breastfeeding. References: Cimaz R, Meregalli E, Biggioggero M, et al:Alterations in the immune system of children from mothers treated with immunosuppressive agents during pregnancy. ToxicolLett2004, 149:155-162. Østensen M, Khamashta M, Lockshin M, et al:Anti-inflammatory and immunosuppressive drugs and reproduction. ArthritisResTher2006, 8:209. McKay DB, Adams PL, Bumgardner GL, et al:Reproduction and pregnancy in transplant recipients:current practices. ProgTransplant.2006;16:127-32. Al-Khader AA, Basri N, Al-Ghamdi, et al:Pregnanciesin renal transplant recipients, with a focus on babies. AnnTransplant.2004;9:65-7. Disclosure of Interest: None Declared